Porosity Influence on the Strength and Elasticity of First-Year Sea Ice. - Brown,J H (1987)
This review of theoretical models of elasticity and flexural strength of sea ice is to establish a baseline for future efforts in experimental and theoretical work in these areas. For example, brine content is not the total porosity of sea ice. Total porosity of sea ice is brine plus gas content. Other factors whichmight influence the models and should be considered in any theoreticaal models for sea ice strengths and elasticity are: Visco-elastic and plastic effects along the failure plane as well as slippage. The distribution and geometry of the pores. Gas porosity must be taken into consideration. Consider other configurations for theoretical models. Surface tension effects on the cohesion of the ice platelets. Effects of solid salts on cold ice.